A retrospective review and multi-specialty, evidence-based guideline for the management of necrotising otitis externa. Issue 6 (5th June 2020) - Hopkins, M E; Bennett, A; Henderson, N; MacSween, K F; Baring, D; Sutherland, R
Abstract: Background: Necrotising otitis externa is a progressive infection of the external auditory canal which extends to affect the temporal bone and adjacent structures. Progression of the disease process can result in serious sequelae, including cranial nerve palsies and death. There is currently no formal published treatment guideline. Objective: This study aimed to integrate current evidence and data from our own retrospective case series in order to develop a guideline to optimise necrotising otitis externa patient management. Methods: A retrospective review of necrotising otitis externa cases within NHS Lothian, Scotland, between 2013 and 2018, was performed, along with a PubMed review. Results: Prevalent presenting signs, symptoms and patient demographic data were established. Furthermore, features of cases associated with adverse outcomes were defined. A key feature of the guideline is defining at-risk patients with initial intensive treatment. Investigations and outcomes are assessed and treatment adjusted appropriately. Conclusion: This multi-departmental approach has facilitated the development of a succinct, systematic guideline for the management of necrotising otitis externa. Initial patient outcomes appear promising.